PROSPEK USAHA PENGOLAHAN BAN BEKAS TERHADAP PENDAPATAN MASYARAKAT PENJUAL DI PASAR BAWAH KOTA PEKANBARU - Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : The development of small industries in Pekanbaru City has received enough attention from the government, remembering its very important role in achieving national development in the long term. This research took place in Pasar Bawah Kota Pekanbaru. This location was chosen because Pasar Bawah is a central market that sells used goods, especially used tires. In this study, sampling for respondents was carried out using the census method, from the used tire processing business unit in the down market of Pekanbaru city which was running well as many as 31 business units. In this study, the authors generally use data analysis using descriptive analysis and quantitative analysis. Descriptive analysis is a research method that aims to collect and analyze data, both primary and secondary, which have a close relationship with the problem under study, to be interpreted descriptively in order to obtain a description of the problem under study, then compare it with theoretical knowledge to proceed with problems and possibilities. the solution. The results showed that this used tire business has prospects because, in terms of its feasibility aspect, using the three calculations, namely NPV, Net B / C, and IRR are declared feasible and profitable. Ownership of used tire business is generally private, the obstacles are still low management or good business processing, it still depends on the seasonality. The capital structure is not strong and access to banks is still minimal.